Respostas
respondido por:
1
3 x + 2 y = - 9
x + y = - 1 multplicando por -2
-2 x - 2 y = 2
3 x + 2 y = - 9
-------------------
x = - 7
substituindo o valor de x
x + y = - 1
-7 + y = - 1
y = -1 + 7
y = 6
S =[ x = - 7 e y = 6 ]
x + y = - 1 multplicando por -2
-2 x - 2 y = 2
3 x + 2 y = - 9
-------------------
x = - 7
substituindo o valor de x
x + y = - 1
-7 + y = - 1
y = -1 + 7
y = 6
S =[ x = - 7 e y = 6 ]
ericaoliveira2002:
nossa muito obrigado , vc me ajudou muito *_*
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás